Kajian Media Sosial dan Kualitas Produk pada Minat Beli Konsumen Kaos Stelabs Startup Business - Marlita, Estiva; Rahmawati, Veronika; M, Santho Vlennery (Indonesian Journal of Management Science, 2022)
Stelabs startup business produces themed t-shirts that are marketed in Surabaya. Stelabs is a new product or business that is also required to create new innovations and promotions that are different from the existing t-shirt business. In addition to promoting products, product quality factors also have an important role in the process of attracting consumer buying interest, especially as a consideration for a consumer in buying a product. This study aims to determine the effect of social media promotion and product quality on consumer buying interest at Stelabs. The study used a quantitative research design with a survey approach. Respondents in this study were 179 respondents. The results of this study indicate that social media promotion has a positive and significant effect on consumer buying interest in Stelabs, so it can be concluded that the better social media provided by Stelabs, the better the influence on consumer buying interest. Product quality has a positive and significant effect on consumer buying interest in Stelabs, so it can be concluded that by improving product quality, consumer buying interest in Stelabs will also increase.